2017
DOI: 10.1128/jcm.00249-17
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Virulent Capnocytophaga canimorsus Isolates by Capsular Typing

Abstract: Capnocytophaga canimorsus is a dog oral commensal that causes rare but severe infections in humans. C. canimorsus was recently shown to be endowed with a capsular polysaccharide implicated in resistance to the innate immune system of the host. Here, we developed the first C. canimorsus capsular serotyping scheme. We describe nine different serovars (A to I), and this serotyping scheme allowed typing of 25/25 isolates from human infections but only 18/52 isolates from dog mouths, indicating that the repertoire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 31 publications
4
47
1
3
Order By: Relevance
“…According to the 16S rDNA phylogenetic analysis, these six strains were, thus, reclassified as C. canis (Supplementary Table S1 ). We then subjected the 96 C. canimorsus sensu stricto strains to the PCR test designed to detect the three A, B, and C capsular serovars 14 . These analyses showed that 87 of the 96 strains were positive and could be further typed as either A, B, or C by serovar-specific PCRs (Table 1 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the 16S rDNA phylogenetic analysis, these six strains were, thus, reclassified as C. canis (Supplementary Table S1 ). We then subjected the 96 C. canimorsus sensu stricto strains to the PCR test designed to detect the three A, B, and C capsular serovars 14 . These analyses showed that 87 of the 96 strains were positive and could be further typed as either A, B, or C by serovar-specific PCRs (Table 1 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, 86 of the 96 C. canimorsus strains tested (89.58%) belonged to either serovars A (30/96, 31.3%), B (28/96, 29.2%), or C (28/96, 29.2%). Next, we tested all strains by PCRs detecting the D and E capsular types 14 . According to these analyses, seven strains belonged to serovar D and none to serovar E (Table 1 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of rapid sequencing and quantification technologies also allowed for additional characterization of the bacterial isolate, confirming the suspected etiological link between the dog bite and clinical presentation. Genomic analyses showed the isolate to be serotype D, which is not commonly found in clinical cases and thus not considered to be highly virulent [6]. The low virulent serovar status is unusual given the patient also did not have significant risk factors for C. canimorsus infection, such as immunosuppression, asplenia, heavy alcohol use, or elderly age [8,[10][11][12].…”
Section: Discussionmentioning
confidence: 95%
“…The patient and dog C. canimorsus genomes were sequenced through a combination of MinION and Illumina sequencing, generating complete genomes which were nearly indistinguishable (Supplementary Materials). A computational analysis of virulence markers[6] indicated the patient isolate was of the Serotype D lineage. No antibiotic resistance markers were identified within the patient isolate genome, which fit the fully susceptible antibiotic profile obtained as part of the culture-based diagnostic investigation (Supplementary Materials).…”
mentioning
confidence: 99%